ANALISIS HIDROLOGI RANCANGAN MENGGUNAKAN METODE RASIONAL PADA SALURAN DRAINASE DI KELURAHAN SUMERTA KELOD KOTA DENPASAR - ANAK AGUNG RATU RITAKA WANGSA; IDA BAGUS SURYATMAJA; A. A. MERI PUJA ANDINI (GANEC SWARA, 2023)
Tukad Kelandis is a tributary of the Tukad Ayung Watershed which is located downstream. In 2021 floods occurred in Tukad Kelandis resulting in one of the places affected by flooding, namely the Art Center area. So it is necessary to do research on the analysis of peak flood discharge on the Tukad Kelandis river using rational methods. Maximum runoff occurs when the rainfall is during the same time as the catchment area concentration time in the rational method. Based on the research results, the amount of planned flood discharge in the Tukad Kelandis watershed was obtained using the rational method for return periods of 2, 5, 10, 20, and 25 years, namely: Q2 Year = 273,890 m3/s, Q5 Year = 337,372 m3/s, Q10 Year = 373,194 m3/ s, Q20 Year = 399,610 m3/ s, Q25 Year = 413,406 m3/ s.